Time to Culture Conversion of Bedaquiline and High-Dose Isoniazid for Drug-Resistant Tuberculosis. (29th August 2022) - Walsh, Kathleen F; Vilbrun, Stalz Charles; Souroutzidis, Ariadne; Ellis, Joshua; Delva, Sobiesyke; Joissaint, Guy; Dupnik, Kathryn M; Joseph, Patrice; Pape, Jean W; Koenig, Serena P
Abstract: Patients with multidrug-resistant tuberculosis who received regimens containing high-dose isoniazid (INH HD ) had similar time to culture conversion and treatment outcomes as patients who received regimens with bedaquiline. INH HD is an inexpensive and safe medication that may contribute additive efficacy in combination regimens.